2006
DOI: 10.4049/jimmunol.176.1.365
|View full text |Cite
|
Sign up to set email alerts
|

Uracil DNA Glycosylase Disruption Blocks Ig Gene Conversion and Induces Transition Mutations

Abstract: Ig gene conversion is most likely initiated by activation-induced cytidine deaminase-mediated cytosine deamination. If the resulting uracils need to be further processed by uracil DNA glycosylase (UNG), UNG inactivation should block gene conversion and induce transition mutations. In this study, we report that this is indeed the phenotype in the B cell line DT40. Ig gene conversion is almost completely extinguished in the UNG-deficient mutant and large numbers of transition mutations at C/G bases accumulate wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 16 publications
4
81
0
Order By: Relevance
“…Although the mechanism of SHM and its target selection is incompletely understood, activation-induced cytidine deaminase (AID) (4,5), which converts cytosine into uracil, for example, in the RGYW motif, initiates SHM by converting a C:G base pair to a U:G mismatch. Removal of the U by uracil-DNA glycosylase (UNG) generates an abasic site in the DNA, which may lead to a variety of base substitutions (6)(7)(8). For the WA motif, it is suggested that after AID-dependent deamination of a cytosine, recognition of the U:G mismatch by mismatch repair protein MutSα (MSH2-MSH6 heterodimer, in which MSH stands for MutS Homolog) leads to the recruitment of DNA polymerase η (Pol η), and with an incision made by UNG the ensuing short-patch repair synthesis results in mutations of A:T pairs to G:C (Fig.…”
Section: π-Cation Stacking | A-to-g Transition | Immunoglobulinmentioning
confidence: 99%
“…Although the mechanism of SHM and its target selection is incompletely understood, activation-induced cytidine deaminase (AID) (4,5), which converts cytosine into uracil, for example, in the RGYW motif, initiates SHM by converting a C:G base pair to a U:G mismatch. Removal of the U by uracil-DNA glycosylase (UNG) generates an abasic site in the DNA, which may lead to a variety of base substitutions (6)(7)(8). For the WA motif, it is suggested that after AID-dependent deamination of a cytosine, recognition of the U:G mismatch by mismatch repair protein MutSα (MSH2-MSH6 heterodimer, in which MSH stands for MutS Homolog) leads to the recruitment of DNA polymerase η (Pol η), and with an incision made by UNG the ensuing short-patch repair synthesis results in mutations of A:T pairs to G:C (Fig.…”
Section: π-Cation Stacking | A-to-g Transition | Immunoglobulinmentioning
confidence: 99%
“…cells, a chicken B-cell line that undergoes SHM in the presence of AID but has limited gene conversion (42). These cells originally express surface IgM and can lose the marker after SHM in the heavy and light chains.…”
Section: Loop Graft Variants Effectively Restrict Hiv-bhagwat and Co-mentioning
confidence: 99%
“…Mutagenesis observed in DT40 cells appears essentially "passive", occurring by saturation of the uracil-DNA glycosylase (UNG) repair pathway. Accordingly, deletion of Ung in DT40 cells results in a sevenfold increase in mutagenesis 120 , implying that a large fraction of the uracils generated by AID are repaired error-free, by base-excision repair or by sister chromatin exchange. All mutations observed are targeted to G or C bases, being almost exclusively transition mutations or G to C and C to G transversion mutations: they thus appear to be generated during replication by copy of unrepaired uracils or by bypass of abasic sites, performed by Rev1 in a translesion process that appears strictly dependent on PCNA monoubiquitination 121,122 .…”
Section: Box 1 | Shm In the Dt40 Cell Line: "Passive" Versus "Active"mentioning
confidence: 99%